ACTN3 genotype is associated with human elite athletic performance - Yang, N.; MacArthur, D. G.; Gulbin, J. P.; Hahn, A. G.; Beggs, A. H.; Easteal, S.; North, K. (The American Journal of Human Genetics, 2003)
There is increasing evidence for strong genetic influences on athletic performance and for an evolutionary "tradeoff" between performance traits for speed and endurance activities.We have recently demonstrated that the skeletalmuscle actin-binding protein a-actinin-3 is absent in 18% of healthy white individuals because of homozygosity for a common stop-codon polymorphism in the ACTN3 gene, R577X. a-Actinin-3 is specifically expressed in fasttwitch myofibers responsible for generating force at high velocity. The absence of a disease phenotype secondary to a-actinin-3 deficiency is likely due to compensation by the homologous protein, a-actinin-2. However, the high degree of evolutionary conservation of ACTN3 suggests function(s) independent of ACTN2. Here, we demonstrate highly significant associations between ACTN3 genotype and athletic performance. Both male and female elite sprint athletes have significantly higher frequencies of the 577R allele than do controls. This suggests that the presence of a-actinin-3 has a beneficial effect on the function of skeletal muscle in generating forceful contractions at high velocity, and provides an evolutionary advantage because of increased sprint performance. There is also a genotype effect in female sprint and endurance athletes, with higher than expected numbers of 577RX heterozygotes among sprint athletes and lower than expected numbers among endurance athletes. The lack of a similar effect in males suggests that the ACTN3 genotype affects athletic performance differently in males and females. The differential effects in sprint and endurance athletes suggests that the R577X polymorphism may have been maintained in the human population by balancing natural selection.